Graphic Design Methods of a Science Museum Exhibition for Children - Kanpat Kalumpahaiti (Graduate School of Institut Seni Indonesia Yogyakarta, 2018)
The graphic design is essential for the science museum exhibition affecting the perception and motivation of children to learn and discover a science experience. the research aims to study the graphic design methods of science museum exhibition for children, to propose the new approach of the graphic design which the most efficient expression to motivate learning of children from age 6 to 9 years old, and to design the graphics module within the temporary exhibition space. this article is the 1st phase to observe the graphic design methods of the science museum exhibition by using the fieldwork case study analysing of literature by selected 27 exhibits from the united Kingdom, Japan, and thailand to compare. also, interviews the 7 experts who are a stakeholder with the research. the result indicated that the graphic design approach of all exhibitions with the consistent. However, the mood and tone vary depending on the exhibit presented, and the role of graphics is different because of the socio-cultural context of each country. the conclusion can be drawn that the study result can be the guide or sources inspiration of further artistic creation and design that is attracting children the further stage of development.